Structured Representation of Drug Indications: Lexical and Semantic Analysis and Object-Oriented Modeling - Duclos, C.; Venot, A. (Methods of Information in Medicine, 2000)
No standardized representation of drug indications is currently available that could be used in drug knowledge bases. We describe an object-oriented representation of indications that should make it possible to develop new tools for selecting drugs and checking prescriptions in computerized drug prescription systems. The model was developed using the results of a lexical and semantic analysis of drug indications, collected into a single file and processed using natural language processing software. It distinguishes both the diseases for which the drug may be given and the efficiency of the drug for a given indication. Two aspects of the model were evaluated: the differences if two independent evaluators filled the attributes independently and the loss of information induced by the use of the model. A system based on this model, making it possible for the physician to select all the drugs satisfying various criteria, is also presented.
Keywords: Drug Indications; Knowledge Base; Information Modeling; Electronic Prescribing